Simulation of fractal like branching microchannel network on rectangular heat sink for single phase flow - Manshoor, Bukhari; Sapit, Azwan; Nordin, Normayati; Hariri, Azian; Salleh, Hamidon; Razali, Mohd Azahari; Zaman, Izzuddin; Khalid, Amir; Ghazali, Mohd Fairusham; Alsayed, Muneer Khalifa (Penerbit Akademia Baru, 2020)
Performance of microelectronic devices has been greatly enhanced owing to the development of the very large-skill technology. However, with the increase of circuit density and operating speed, more heat was generated by the microelectronics devices. So, the objective of this project is to do a comparative study between two different types of fractal microchannel at the same size and boundary condition by using Computational Fluid Dynamics (CFD) Besides that, this study also will investigate the hydrodynamic and thermal characteristics of T-shaped and Treeshaped fractal microchannel network heat sinks by solving three-dimensional Navier– Stokes equations and energy equation, taking into consideration the conjugate heat transfers in microchannel walls. For the simulation, ANSYS software was used with the inlet temperature set to be 300 K, inlet velocity will be in the range of 0.1 m/s to 0.5 m/s and uniform heat flux be set at 325 W/cm2. From this study, it was found that due to the structural limitation of right-angled fractal-shaped microchannel network, hotspots may appear on the bottom wall of the heat sink where the microchannel are sparsely distributed. With slight modifications in both fractal-shaped structure of microchannel network, great improvements on the hydrodynamic and thermal performance of heat sink can be achieved. A comparison of the performance of modified fractal-shaped microchannel network heat sink with parallel microchannel heat sink is also conducted numerically based on the same heat sink dimensions. It is found that the modified fractal-shaped microchannel network is much better in terms of thermal resistance and temperature uniformity under the conditions of the same pressure drop or pumping power. Therefore, the modified fractal-shaped microchannel network heat sink appears promising to be used for microelectronic cooling in the future.